Identification of a Novel Functional Corticotropin-Releasing Hormone (CRH2) in Chickens and Its Roles in Stimulating Pituitary TSHβ Expression and ACTH Secretion - Bu, Guixian; Fan, Jie; Yang, Ming; Lv, Can; Lin, Ying; Li, Jinxuan; Meng, Fengyan; Du, Xiaogang; Zeng, Xianyin; Zhang, Jiannan; Li, Juan; Wang, Yajun (Frontiers in Endocrinology, 2019)
Corticotropin-releasing hormone (CRH), together with its structurally and functionally related neuropeptides, constitute the CRH family and play critical roles in multiple physiological processes. Recently, a novel member of this family, namely CRH2, was identified in vertebrates, however, its functionality and physiological roles remain an open question. In this study, using chicken (c-) as the animal model, we characterized the expression and functionality of CRH2 and investigated its roles in anterior pituitary. Our results showed that (1) cCRH2 cDNA is predicted to encode a 40-aa mature peptide, which shares a higher amino acid sequence identity to cCRH (63%) than to other CRH family peptides (23–38%); (2) Using pGL3-CRE-luciferase reporter system, we demonstrated that cCRH2 is ~15 fold more potent in activating cCRH receptor 2 (CRHR2) than cCRHR1 when expressed in CHO cells, indicating that cCRH2 is bioactive and its action is mainly mediated by CRHR2; (3) Quantitative real-time PCR revealed that cCRH2 is widely expressed in chicken tissues including the hypothalamus and anterior pituitary, and its transcription is likely controlled by promoters near exon 1, which display strong promoter activity in cultured DF-1 and HEK293 cells; (4) In cultured chick pituitary cells, cCRH2 potently stimulates TSHβ expression and shows a lower potency in inducing ACTH secretion, indicating that pituitary/hypothalamic CRH2 can regulate pituitary functions. Collectively, our data provides the first piece of evidence to suggest that CRH2 play roles similar, but non-identical, to those of CRH, such as its differential actions on pituitary, and this helps to elucidate the roles of CRH2 in vertebrates.